Farmer-livestock keepers land Use conflicts in the Kilombero Valley Floodplain, Morogoro Region, Tanzania - Thebe, Vusilizwe (University of Pretoria, 2025)
Thesis (PhD (Development Studies))--University of Pretoria, 2024.